MODEL PENINGKATAN INOVASI BERBASIS ORIENTASI PASAR, KNOWLEDGE SHARING DAN ORIENTASI PEMBELAJARAN TERHADAP KINERJA BISNIS - Moch Zulfa; Choirul Umam (Jurnal Ekonomi dan Bisnis, 2018)
in this study is to find and analyze the influence of orientasipasar , knowledge sharingand orientation learning of the performance of business with variable innovation as variable nointervening on industrial flour tapioca in kabupaten Pati. A population that used is the owner /entrepreneurs on industrial flour tapioca in kabupaten Pati of 162 people. Based on the resultsof the spread of the questionnaire directly to owners and with using a technique the samplecollection simple random sampling, so obtained the sample of the of 66 respondents instrumentthe analysis is the path analysis with the program spss, where formerly undergone a validityand reliability and test the assumption classical. The results of testing shows that marketorientation knowledge sharing and orientation of learning shown to have a positive influence toinnovation and business performance .Innovation have a positive influence on the performanceof business , can be defined that the more the owner / entrepreneurs be able to create newproduct innovation , the more one is increase the business performance produced .Innovationcapable of being variable intervening between market orientation with the performance ofbusiness , it means the higher market orientation , The owner of the / employers could know ,understand and answer the needs and hope from customers , so that the owner / entrepreneurswill be created product innovation new in increase the business performance . Innovation notcapable of being variable no intervening between knowledge sharing with the performance ofbusiness.Innovation capable of being variable no intervening between orientation learning withthe performance of business, Can be defined the higher the owner / entrepreneurs have theability to learn, will it increases or insight new so will create product innovation new so increasethe performance of business.Keyword: orientation market, knowledge sharing, orientation learning, innovation andperformance busines